Actigraphy to Evaluate Changes in Physical Activity After Autologous Breast Reconstruction- A Prospective Comparison Study: Actigraphy to Evaluate Changes in Physical Activity After Autologous Breast Reconstruction- A Prospective Comparison Study - PRUSTY, KRISHNA PRASAD (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Background-Early ambulation and return to preoperative (baseline) ambulatory level is protective against postoperative venous thromboembolism. The duration of decreased physical activity after surgery is unknown for most procedures, as surgeons typically estimate physical recovery based on subjective patient reporting. Objectives- To quantify the time it takes to return to baseline ambulatory status after breast reconstruction using actigraphy devices. Methods- Actigraphy devices were used to evaluate preoperative and postoperative physical activity levels in patients undergoing autologous breast reconstruction at a tertiary care institution. Steps and resting heart rate (HR) were used as metrics of physical activity and physiological state. "Baseline" physical activity was defined by the average daily step count during the 14 days before surgery. "Return to baseline" occurred when the 7-day daily step average was greater than or equal to 95% of their baseline steps. SPSS (version 22.0) was used for analysis. Results- From May 2020 to April 2021, 30 patients were enrolled in the study before deep inferior epigastric perforator breast reconstruction. The mean age was 49.2 years and mean BMI was 28.6. This cohort averaged 7918 ± 3271 preoperative steps. Two patients returned to baseline activity by postoperative day 28. In total, 8 patients returned by postoperative week 8. Preoperative resting HR average was 73.4 ± 9.33 beats per minute. Actigraphy data demonstrated an initial decrease in activity,increase in sleep variability and increased heart rate that approached the patients’pre-operative normalized data as they recovered over time. Conclusions:These data demonstrate that actigraphy data would be of interest topatients making breast reconstruction decisions and that the data can be successfullycollected to inform decision-making. These findings indicate that surgeons may underestimate the impact of surgery on physical decline and, consequently, may undertreat with venous thromboembolism prophylaxis.